Diversidade taxonômica, funcional e genética da comunidade zooplanctônica do Reservatório do Lobo (Broa, SP-Brasil), em diferentes escalas temporais - Paina, Karime de Araujo (2023)
Nowadays, concerns about various aspects of environmental issues have become very frequent, especially those related to climate change. In this sense, studying and measuring the biodiversity of aquatic ecosystems is, without a doubt, one of the many ways we can think and act in favor of environmental conservation. Freshwater aquatic ecosystems, environments of great importance for the maintenance of our planet, have suffered the consequences of human activities in recent decades. Among these environments, reservoirs, especially, deserve to be highlighted, as they play an important role in terms of impacts on local biodiversity and benefits to the human species in several ways. In this work, we sought to analyze how climate change can impact aquatic ecosystems, especially affecting zooplankton communities, through the study of a tropical reservoir in southeastern Brazil. We carried out a historical analysis of the last five decades to verify how recent climate changes have impacted the dynamics of these communities over the years. Also, focusing on these important groups that are close to the base of the trophic chain, we sought to analyze and measure the diversity of these organisms through attributes and functional analyses. To characterize the zooplankton community, we sought to classify the three most important groups – Rotifera, Cladocera, and Copepoda – using molecular tools. Collections of the zooplankton community were carried out monthly for a period of two years, from May 2019 to April 2021, in the Lobo-Broa Reservoir. The data collected during this period, along with recent studies, were grouped with those of the historical survey of the last fifty years, that is, since the beginning of study activities in this environment. For diversity analyses, the zooplankton species were characterized according to their functional attributes and grouped based on their functionality in the ecosystem, among Rotifera, Cladocera, and Copepoda. For a greater understanding of the entire zooplankton community, based on molecular analyses, the DNA of each species was extracted and sequenced for analysis of the COI molecular marker – barcoding, to build a library of molecular data for zooplankton, as this information is still scarce for Brazilian aquatic environments.